2016
DOI: 10.3389/fpsyg.2016.01625
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Technical Reasoning More Than Functional Knowledge in Development of Tool Use in Childhood

Abstract: It is well-known that even toddlers are able to manipulate tools in an appropriate manner according to their physical properties. The ability of children to make novel tools in order to solve problems is, however, surprisingly limited. In adults, mechanical problem solving (MPS) has been proposed to be supported by “technical reasoning skills,” which are thought to be involved in every situation requiring the use of a tool (whether conventional or unusual). The aim of this study was to investigate the typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…Instead, it appears that children's success suffered due to a failure to integrate the perceptual feedback of their tool manipulation to the target object (Gardiner et al, 2012;van Leeuwen et al, 1994), or a lack of fine motor skills (Bechtel et al, 2013), rather than due to a limitation of their affordance understanding. This reflects previous research demonstrating that young children are better at selecting or constructing a tool appropriate for a task than they are at successfully using it to achieve a goal (Gardiner et al, 2012;Remigereau et al, 2016). Many children on the current task made an ideal innovation on their pipecleaner, but often this action was not finalized to an adequate degree to make it long enough or straight enough to go cleanly down the tube and reach the bucket.…”
Section: Discussionsupporting
confidence: 74%
“…Instead, it appears that children's success suffered due to a failure to integrate the perceptual feedback of their tool manipulation to the target object (Gardiner et al, 2012;van Leeuwen et al, 1994), or a lack of fine motor skills (Bechtel et al, 2013), rather than due to a limitation of their affordance understanding. This reflects previous research demonstrating that young children are better at selecting or constructing a tool appropriate for a task than they are at successfully using it to achieve a goal (Gardiner et al, 2012;Remigereau et al, 2016). Many children on the current task made an ideal innovation on their pipecleaner, but often this action was not finalized to an adequate degree to make it long enough or straight enough to go cleanly down the tube and reach the bucket.…”
Section: Discussionsupporting
confidence: 74%
“…This close relationship between sensorimotor and semantic information is particularly evident for the acquisition of knowledge about tools and artifacts. As has been discussed above, during learning, the manipulation knowledge that is acquired by haptics and vision is linked to functional knowledge about the contexts and conditions of using the respective artifact (Remigereau et al 2016). Hence, taken together, the findings indicate that haptic exploration contributes to a rich multimodal representation which may also be linked to abstract concepts, thereby facilitating retention and transfer.…”
Section: Processing In Working Memory and Storage In Long-term Memorymentioning
confidence: 58%
“…For example, Gredlein and Bjorklund (2005) found that children who engaged in manual play with a range of objects during free play were more successful in choosing appropriate tools for solving a task in a later situation. Furthermore, manipulation knowledge which is acquired by haptics and vision is linked to functional and mechanical knowledge (Remigereau et al 2016). Whereas functional knowledge concerns information about the context in which a tool can be used together with the objects usually used with that tool, mechanical knowledge addresses the underlying physical and technical principles, allowing one to form a mental simulation of the tool use in action (Osiurak and Badets 2016;Remigereau et al 2016).…”
Section: Acquiring Knowledge About Tools and Artifacts Via Object-basmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect has been elegantly demonstrated by Baillargeon and colleagues, who have shown how the principle of support evolves in early childhood (6 months: Infants consider any amount of contact between the object and the support sufficient for the object to be supported; 6-9 months: Infants expect an object to remain stable if a significant portion of its surface is in contact with the support; 9 months: Infants understand that other features such as the mass distribution of an object is critical to determine whether a support is appropriate or not, and so on; Baillargeon & Hanko-Summers 1990;Baillargeon et al 1992;Needham & Baillargeon 1993). These findings indicate that mechanical knowledge can be acquired relatively early in childhood and can continue to grow over time (Remigereau et al 2016), even during adulthood. In this respect, mechanical knowledge is never completely accurate and can be the basis for some "magical" beliefs such as thinking that any amount of contact between an object and a support is sufficient for the object to be supported.…”
Section: Mechanical Knowledge Is "A Kind Of Magic"mentioning
confidence: 99%